(untitled) (Sociologisk Forskning, 2022)
Ever since the Convention of the Rights of the Child, we have seen a wide variety of interpretations on the meaning of “children’s participation.” A critical perspective, based on a social phenomenology, is here suggested to disclose the taken-for-grantedness implicit in both policy and theoretical accounts relating to the phenomenon of children’s participation. Within the situation of family law proceedings in Sweden, children’s participation will be explored in relation to its intersubjective constitution in the social world and in the manifold of sub-worlds in which it appears. It is argued that a social phenomenological approach makes it possible to explicate what we mean by children’s participation in the context of policy within the situation of family law proceedings, and to thus open up for a way to approach this phenomenon based on critical reflection.